Regional contribution of vascular dysfunction in white matter dementia: clinical and neuropathological insights - Pansieri, Jonathan; Hadley, Gina; Lockhart, Andrew; Pisa, Marco; DeLuca, Gabriele C. (Frontiers in Neurology, 2023)
The maintenance of adequate blood supply and vascular integrity is fundamental to ensure cerebral function. A wide range of studies report vascular dysfunction in white matter dementias, a group of cerebral disorders characterised by substantial white matter damage in the brain leading to cognitive impairment. Despite recent advances in imaging, the contribution of vascular-specific regional alterations in white matter dementia has been not extensively reviewed. First, we present an overview of the main components of the vascular system involved in the maintenance of brain function, modulation of cerebral blood flow and integrity of the blood-brain barrier in the healthy brain and during ageing. Second, we review the regional contribution of cerebral blood flow and blood-brain barrier disturbances in the pathogenesis of three distinct conditions: the archetypal white matter predominant neurocognitive dementia that is vascular dementia, a neuroinflammatory predominant disease (multiple sclerosis) and a neurodegenerative predominant disease (Alzheimer’s). Finally, we then examine the shared landscape of vascular dysfunction in white matter dementia. By emphasising the involvement of vascular dysfunction in the white matter, we put forward a hypothetical map of vascular dysfunction during disease-specific progression to guide future research aimed to improve diagnostics and facilitate the development of tailored therapies.